Pertimbangan Hakim Dalam Penetapan Wali Khusus Anak Asuh di Lembaga Kesejahteraan Sosial Anak (Studi Penetapan Nomor: 221/Pdt.P/2024/PN.Tjk) - Hefrianto, Wafi Rizqullah; Baharrudin, Baharrudin; Aprinisa, Aprinisa (Journal of Law, Education and Business, 2025)
Guardianship for minors is a form of oversight over the personal and property rights of children who have not reached adulthood and are not under parental authority, aimed at providing optimal legal protection for the child. Child guardianship is typically filed through a court application, in accordance with the requirements stipulated in legislation and established procedures. Guardianship involves granting custody rights to individuals or legal entities over minors under specific conditions, such as when the child has no parents, the parents are unable to fulfill their responsibilities, or the whereabouts of the parents are unknown. This study aims to analyze the judicial considerations in appointing a special guardian for foster children in Child Social Welfare Institutions (LKSA), focusing on the case of Decision Number: 221/Pdt.P/2024/PN.Tjk. This issue is significant, considering that foster children are a vulnerable group requiring legal protection to ensure their rights, including education, care, and welfare, are fulfilled. The research employs a normative and empirical juridical approach. Data sources include both normative and empirical data. Data collection methods involve library research and field research. The data analysis technique used is qualitative juridical analysis. The findings reveal that in Decision Number: 221/Pdt.P/2024/PN.Tjk, the court considered several crucial aspects, such as the absence of biological parents, the inability of the family to provide care, and the importance of legal protection for the child’s rights, including inheritance management and key decision-making. In this ruling, the court appointed Budi Hidayat, the head of the Bussaina Lampung Foundation LKSA, as the special guardian for Muhammad Hafidz, a six-year-old child under the care of the institution. The court's considerations in this case encompass legal aspects, including the fulfillment of legal requirements as stipulated in Articles 50-54 of the Civil Code and the Child Protection Act, as well as taking into account the social and psychological conditions of the child and the ability of the proposed guardian to meet the child’s needs.